Impact of remote working on employees‘ performance and satisfaction - Smutná, Lenka; Pauknerová, Daniela, 1970-; Králová, Tereza, 1978-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The purpose of this thesis is to examine the impact of remote working policies of a certain company on its employees. The main areas of interest are employees' performance and satisfaction. The thesis is divided into two parts, theoretical and practical. The theoretical part provides an overview of the origins and definition of remote working, the approach of companies worldwide and the impact of the COVID-19 pandemic. Additionally, the benefits and drawbacks of remote working are examined in detail. In the practical part of the thesis, a case study of company A is conducted. Interviews with team leaders and questionnaires distributed among their subordinates were used to assess their satisfaction with the company-specific remote working policies. The findings reveal that employees are generally happy with the remote working regulation in the company, with many reporting increased job satisfaction due to greater flexibility and work-life balance. The paper concludes with a recommendation for company A to consider bigger flexibility in the remote working regulation.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses